2023
DOI: 10.1039/d3em00074e
|View full text |Cite
|
Sign up to set email alerts
|

Chemical species of cesium and iodine in condensed vaporized microparticles formed by melting nuclear fuel components with concrete materials

Abstract: The condensed vaporized microparticles (CVMPs) were formed by melting CsI with concrete. After the water treatment of CVMPs, some portions of Cs remained with Si in the CVMPs, even though most of the Cs and I were dissolved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Preliminary investigations have demonstrated the feasibility of generating microparticles resembling CsMPs in shape and size, along with a comparable chemical composition, through small-scale MCCI experiments ( 20 g of reagents) in the VITI furnace at the CEA Cadarache 24 . Simultaneously, another research team observed similar results while simulating MCCI using a distinctly different experimental setup 25 . Consequently, additional experiments in the VITI furnace, coupled with more in-depth analyses, have been conducted to reinforce the theoretical framework and gain a nuanced understanding of the generation mechanism of type-A particles.…”
Section: Introductionmentioning
confidence: 57%
“…Preliminary investigations have demonstrated the feasibility of generating microparticles resembling CsMPs in shape and size, along with a comparable chemical composition, through small-scale MCCI experiments ( 20 g of reagents) in the VITI furnace at the CEA Cadarache 24 . Simultaneously, another research team observed similar results while simulating MCCI using a distinctly different experimental setup 25 . Consequently, additional experiments in the VITI furnace, coupled with more in-depth analyses, have been conducted to reinforce the theoretical framework and gain a nuanced understanding of the generation mechanism of type-A particles.…”
Section: Introductionmentioning
confidence: 57%